2014
DOI: 10.1007/s10815-014-0349-2
|View full text |Cite
|
Sign up to set email alerts
|

Composition of protein supplements used for human embryo culture

Abstract: The composition of protein supplements are variable, consisting of previously undescribed components. High concentrations of pro-oxidant transition metals were most notable. Blastocyst development was protein dependent and showed an interaction with oxygen concentration and pro-oxidant supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…Primers for genes previously correlated with embryo viability [6,32,33] (bone morphogenic protein 15, Bmp15; caudaltype homeobox protein 2, Cdx2; cyclooxgenase 2, Cox2; DNA methyltransferase 3a, Dnmt3a; glutaredoxin2, Glrx2; glucose transporter 1, Glut1; octamer-binding protein 4, Oct4), and the reference gene peptidylprolylisomerase A (Ppia) were designed for quantitative PCR (qPCR) using Primer3 [31], and qPCR was performed as previously described [6,32,33]. Accession number, primer sequence, and product length of target and reference genes are described in Supplemental Table 1.…”
Section: Quantitative Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Primers for genes previously correlated with embryo viability [6,32,33] (bone morphogenic protein 15, Bmp15; caudaltype homeobox protein 2, Cdx2; cyclooxgenase 2, Cox2; DNA methyltransferase 3a, Dnmt3a; glutaredoxin2, Glrx2; glucose transporter 1, Glut1; octamer-binding protein 4, Oct4), and the reference gene peptidylprolylisomerase A (Ppia) were designed for quantitative PCR (qPCR) using Primer3 [31], and qPCR was performed as previously described [6,32,33]. Accession number, primer sequence, and product length of target and reference genes are described in Supplemental Table 1.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…product should be used for clinical ART. The more troubling scenario is the possibility that a product could support the development of murine embryos but still be unsuitable for clinical use [3,6]. The key to preventing such products from entering the clinic is to improve the sensitivity of MEAs and ensure clinically relevant results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that both HSA and complex protein supplements are heterogeneous in nature [19] and thus represent variation that may impact MEA results. Specifically, complex proteins (SPS, LGPS) contain more transition metals than other protein supplements which may increase reactive-oxidant species and result in cell damage [18]. This study found SPS increased toxicity while HSA did not affect sensitivity.…”
Section: Discussionmentioning
confidence: 78%
“…For human IVF, decreased oxygen concentration (5%) is both physiologic in the reproductive tract and associated with improved outcomes [13][14][15][16], yet many IVF clinics throughout the world still use atmospheric oxygen for culture and for QC testing [17]. The type of protein also varies in practice, thus, representing another variable that could influence assay sensitivity [18,19]. A third variation in embryo culture methods, group versus individual culture, influences QC sensitivity [10], and evidence suggests that group culture improves IVF outcomes, either through diffusion of unknown paracrine factors or maintenance of a stable microenvironment [20].…”
Section: Introductionmentioning
confidence: 99%